Yearbook of the United Nations 2002 - Nations Unies (United Nations, 2002)
The Yearbook of the United Nations provides an indispensable A-Z reference on the United Nations. This new and fully updated edition covers all the major activities undertaken in the United Nations system in 2002. A must-have title for library reference collections, the Yearbook of the United Nations is widely consulted by diplomats, government officials, scholars, journalists and others with a serious interest in international affairs.